Arachidonic acid activation of a new family of K+ channels in cultured rat neuronal cells. - Kim, D (1995)
1. The presence and properties of K+ channels activated by arachidonic acid were studied in neuronal cells cultured from the mesencephalic and hypothalamic areas of rat brain. 2. Arachidonic acid produced a concentration-dependent (5-50 microM) and reversible activation of whole-cell currents. 3. In excised membrane patches, arachidonic acid applied to the cytoplasmic or extracellular side of the membrane caused opening of three types of channels whose current-voltage relationships were slightly outwardly rectifying, inwardly rectifying and linear, and whose single channel slope conductances at +60 mV were 143, 45 and 52 pS, respectively. 4. All three currents were K+ selective and blocked by 2 mM Ba2+ but not by other K+ channel blockers such as tetraethylammonium chloride, 4-aminopyridine and quinidine. The outwardly and inwardly rectifying currents were slightly voltage dependent with higher channel activity at more depolarized potentials. 5. Arachidonic acid activated the K+ channels in cells treated with cyclo-oxygenase and lipoxygenase inhibitors (indomethacin and nordihydroguaiaretic acid), indicating that arachidonic acid itself can directly activate the channels. Alcohol and methyl ester derivatives of arachidonic acid failed to activate the K+ channels, indicating that the charged carboxyl group is important for activation. 6. Certain unsaturated fatty acids (linoleic, linolenic and docosahexaenoic acids), but not saturated fatty acids (myristic, palmitic, stearic acids), also reversibly activated all three types of K+ channel. 7. All three K+ channels were activated by pressure applied to the membrane (i.e. channels were stretch sensitive) with a half-maximal pressure of approximately 18 mmHg. The K+ channels were not blocked by 100 microM GdCl3. 8. A decrease in intracellular pH (over the range 5.6-7.2) caused a reversible, pH-dependent increase in channel activity whether the channel was initially activated by arachidonic acid or stretch. 9. Glutamate, a neurotransmitter reported to generate arachidonic acid in striatal neurons, did not cause activation of the K+ channels when applied extracellularly in cell-attached patches. 10. It is suggested that the K+ channels described here belong to a distinct family of ion channels that are activated by either fatty acids or membrane stretch. Although the physiological roles of these K+ channels are not yet known, they may be involved in cellular processes such as cell volume regulation and ischaemia-induced elevation of K+ loss.